2021
DOI: 10.1017/s0022215121003819
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising otitis externa: a serious condition becoming more frequently encountered

Abstract: Background Necrotising otitis externa is an aggressive infection of the external ear, which extends to the surrounding bone and soft tissue. In recent years, there has been an apparent increase in the number of patients admitted to our hospital with this condition. Methods A retrospective review was conducted of all patients admitted to our hospital with necrotising otitis externa between July 2012 and June 2020. Results Among 39 patients included, only 9 were diagnosed in the first four years, and 30 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The facial nerve is often involved. Sigmoid sinus involvement causes retrograde thrombophlebitis [3,7]. Intracranial extension results in the involvement of opposite skull bases [1,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The facial nerve is often involved. Sigmoid sinus involvement causes retrograde thrombophlebitis [3,7]. Intracranial extension results in the involvement of opposite skull bases [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant otitis externa (MOE) is a misnomer since it is not a neoplastic process [1]. It implies an aggressive inflammation of the external auditory canal in elderly diabetic, and immunocompromised individuals with Pseudomonas aeruginosa as the main culprit followed by methicillin-resistant Staphylococcus aureus and other fungal organisms [2,3]. The inflammatory process is so fierce that it may involve the skull base leading to Skull Base Osteomyelitis [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This scoring system uses inherent patient factors rather than the usual disease severity related assessments, so might help raise vigilance in patients who could otherwise be seen as relatively low risk based on disease status alone. Eweiss and colleagues from Essex, UK, 6 found that the incidence of necrotising otitis externa in their geographical area had increased dramatically in recent years, with cases sometimes and surprisingly involving immunocompetent patients.…”
mentioning
confidence: 99%
“…Improving outcomes in necrotising otitis externa, telephone clinics, and topical pimecrolimus for chronic eczematous external otitis Jonathan Fishman and Edward Fisher, Editors Necrotising otitis externa is an aggressive infection of the external ear, the incidence of which is increasing. [1][2][3][4] The optimal strategy for the diagnosis and management of necrotising otitis externa remains uncertain, and there is considerable variability in how the condition is managed. 5,6 Several articles in this month's issue of The Journal of Laryngology & Otology address this condition.…”
mentioning
confidence: 99%